DECISION MAKING: Sebuah Telaah Awal - Ermi Sola (Idaarah: Jurnal Manajemen Pendidikan, 2018)
AbstractIn general, decision making is a process of choosing alternatives conducted by a certain people in an organization. An accurate decision that solves or answers the problem, needs ...and creativity from the decision makers. The decision makers have to follow any steps of decision making itself. Generally, there many steps in decision making, starting from the clearness of problem it self, develop alternatives, assess the alternatives by determine certain criteria, choose the best alternatives to be a decision, implement it, and control the implementation especially to the decision that is not routine, rarely happens, and special. Judgement, intuition, and creativity is the key to a success and effective decision making.